Rasa kesepian dan adiksi ponsel cerdas: Kontrol diri sebagai moderator - Suarni, Waode (Jurnal Psikologi Ulayat, 2025)
Loneliness and smartphone addiction are relatively common phenomena in everyday life. A number of studies have shown the association between them, but little is known about the mechanisms underlying the relationship. This study aims to explore the possible mediating role of mobile attachment and the moderating role of self-control in the relationship between loneliness and smartphone addiction. A total of 163 university students (18 men, 145 women) aged between 18 and 20 years, participated in this study. The relationships among the research variables were tested using the PROCESS moderated-mediation model. The results show that: (1) loneliness positively predicts smartphone addiction, (2) mobile attachment partially mediates the relationship between loneliness and smartphone addiction, and (3) the loneliness effect on smartphone addiction is moderated by self-control. These findings highlight the importance of strengthening self control skills and addressing emotional reliance on mobile phones in efforts to reduce smartphone addiction among young adults